Pengaruh Komunikasi Terapeutik terhadap Kepuasan Pasien dalam Pelayanan di Klinik Pelangi Bunda Medika - Uswatun Hasanah; Noerma Kurnia Fajarwati; Meiby Zulfikar; Eka Susilawati; Arfian Suryasuciramdhan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to determine the effect of therapeutic communication on patient satisfaction with services at the Pelangi Bunda Medika Clinic. The study employed a quantitative approach with a causal associative method, focusing on the relationship between health workers’ communication behavior and patient responses to the quality of care received. Data were collected through questionnaires distributed to 100 outpatients who had received services within the last three months, ensuring that the sample reflected recent patient experiences. The analysis techniques included validity and reliability tests to confirm instrument accuracy, descriptive analysis to summarize patient perceptions, normality testing, simple linear regression to examine causal influence, and hypothesis testing for statistical confirmation. The results revealed that therapeutic communication was categorized as very high (89.63%), characterized by clarity of information, empathy, and active listening by health personnel. Meanwhile, patient satisfaction was categorized as high (88.63%), reflecting positive evaluations of service quality, staff attitude, and comfort during treatment. The regression test showed a significant and positive effect, with a t-value of 10.608 > t-table 1.984 and a significance value of 0.000. The coefficient of determination (R²) was 0.534, indicating that therapeutic communication accounted for 53.4% of patient satisfaction, while the remainder was influenced by other factors such as facilities and waiting time. These findings support the S-O-R theory, where therapeutic communication (stimulus) is processed by the patient (organism) to generate satisfaction (response). The study emphasizes the crucial role of empathetic and professional communication in enhancing the quality of primary health services.